Determinants of using the services of the Łódzka Kolej Aglomeracyjna - Frankiewicz, Eliza (Developing Sustainable, Smart and Resilient Urban Transportation Systems - Residents' Perspective, 2024)
This chapter of the monograph combines theoretical and empirical analysis to investigate the key aspects related to improving the accessibility and competitiveness of agglomeration railways compared to individual transportation. It focuses on selected issues relevant to the topic, with a primary objective of evaluating the current state of the Łódź Agglomeration Railway system and identifying its future prospects.The study aims to determine the advantages and disadvantages of implementing transport services by Łódzka Kolej Aglomeracyjna Sp. z o.o., while identifying potential areas for improvement and recognizing the needs of the company's customers. An anonymous internet survey was used as the research method. The content of this chapter provides important insights that may contribute to further research on the development and significance of agglomeration railways in Łódź.